Impact of substance use patterns on caregivers’ quality of life, mood and burden: a cross-sectional study in Egypt - Rehab Mohamed Naguib; Mona Mahmoud El-Sheikh; Tarek Galal Elsamman Abdellah Khlel Alqadi; Sara Abdelkader El-awady (Middle East Current Psychiatry)
Abstract Background Substance use disorder affects not only the individual struggling with misuse but also their caregivers’ quality of life. Investigating the impact on caregivers of patients with substance use disorder in Egypt can improve our understanding of their problem and enhance our management plan. Objective To assess and compare the quality of life, mood, and burden among caregivers of substance use disorder inpatients and outpatients, then to examine the correlation between the quality of life among the caregivers and the pattern and severity of substance use, in addition to other sociodemographic factors. Methods This cross-sectional-comparative study, conducted at the Institute of Psychiatry, Ain Shams University, Egypt, involved 126 caregivers of substance use disorder patients, divided into two groups (outpatient and inpatient), between July 2023 and January 2024. The Addiction Severity Index and the Structured Clinical Interview for Mental Disorders- 1 are used for patients, while the World Health Organization, Zarit Burden scale, Beck Depression Inventory, and General Health Questionnaire are used for caregivers. Results Substance dependence affects the quality of life of caregivers of both groups, more among inpatient groups, with the highest presentation of very poor quality of life and severe burden among caregivers of stimulant users, while the highest percentage of depressive symptoms among caregivers of patients using alcohol. Regression analysis showed that caregivers’ quality of life is dependent on the following: overdose history, age of first use, socioeconomic worsening, and family factor of addiction severity index. Conclusion The study found that substance use disorder negatively impacts caregivers’ quality of life, particularly those with a history of overdose and early onset, leading to deterioration in caregiver burden. Stimulant use disorder has a greater impact on caregiver burden and quality of life compared to other substances.